Carbon‐based light‐induced thermoelastic spectroscopy for ammonia gas sensing. Issue 5 (6th January 2022) - Wang, Yu; Cheng, Tong; Lou, Cunguang; Liu, Xin; Li, Xitong; Huang, Lei; Yao, Jianquan; Liu, Xiuling
Abstract: A light‐induced thermoelastic spectroscopy (LITES) based on carbon nanotubes (CNT), graphene oxide (GO), and reduced graphene oxide (rGO) coated quartz tuning fork (QTF) was proposed. In order to improve the conversion efficiency of laser energy radiation into the vibration of tuning fork, thin CNT, GO, and rGO layers were coated on the surface of commercial QTF, respectively. Ammonia (NH3 ) gas was selected as the target analyte for the experimental validation. The experimental results show that the system's maximum gain factor in signal amplitude and signal‐to‐noise ratio (SNR) are 1.52, 1.53, 2.43, and 1.54, 1.33, 2.24 times, respectively, as compared with the traditional LITES with bare QTF.